The Effectiveness of Community-Based Continuous Training on Promoting Positive Behaviors towards Birth Preparedness, Male Involvement, and Maternal Services Utilization among Expecting Couples in Rukwa, Tanzania: A Theory of Planned Behavior Quasi-Experimental Study - Moshi, Fabiola V. (J Environ Public Health, 2018)
BACKGROUND: Rukwa Region has the highest maternal mortality ratio, 860 deaths per 100,000 live births in Tanzania. The region has neonatal mortality rate of 38 deaths per 1,000 live births. Previous interventions to promote maternal and neonatal health targeted access to maternal services by removing financial barriers and increasing the number of health facilities. However, maternal service utilization remains very low, especially facility delivery. The proposed intervention was sought to address deep-rooted behavioral beliefs, normative beliefs, control beliefs, and knowledge empowerment to determine their effect on improving birth preparedness, male involvement, and maternal services utilization. The study tested the effectiveness of a Community-Based Continuous Training (CBCT) intervention that was based upon the theory of planned behavior and was sought to promote positive behaviors. METHODS: The study used a quasi-experimental design. The design consisted of pre- and postintervention assessments of two nonequivalent groups. Two districts were selected conveniently using criteria of high home birth. A district to hold intervention was picked randomly. Study participants were expecting couples at gestation age of 24 weeks and below. After obtaining informed consents, participants were subjected to baseline assessment. Expecting couples in the intervention group had two training sessions and two encounter discussions. The three primary outcomes of the study were changes in the level of knowledge about birth preparedness, male involvement, and use of maternal services. Data were collected at preintervention, midintervention, and postintervention. Policy Implications of the Results. The aim of this paper was to describe the study protocol of a quasi-experimental study design to test the effectiveness of an interventional program on promoting positive behaviors on birth preparedness, male involvement, and maternal services utilization among expecting couples. This study has a potential to address the challenge of low birth preparedness, male involvement, and use of maternal health services in Rukwa Region.